Influence of Debt To Total Asset Ratio (DAR) Current Ratio (CR) and Total Asset Turnover (TATO) on Return On Asset (ROA) and Its Impact on Stock Prices on Mining Companies on the Indonesia Stock Exchange in 2008-2017 - ZAMAN, MUHAMAD BADRU (AGUSPATI Research Institute, 2021)
This study aims to determine the effect of Debt To Total Asset Ratio (DAR) Current Ratio (CR) and Total Asset Turnover (TATO) on Return On Asset (ROA) and Its Impact on Stock Prices on Mining Companies on the Indonesia Stock Exchange in 2008-2017.Data collection was carried out by taking secondary data in the form of 8 companies' financial statements for the period 2008 - 2017 where financial statements were made panel data and processed with software Eviews 9.0. The analytical method used is an associative descriptive analysis. Data analysis includes data feasibility tests, regression analysis, and hypothesis testing partially and simultaneously.The results of this study indicate that (1) the effect of Debt To Asset Ratio (DAR) on Return On Assets (ROA) has a positive insignificant effect, (2) the effect of Current Ratio (DER) on Return On Assets (ROA) has a significant positive effect, (3) the effect of Total Asset Turnover (TATO) on Return On Assets (ROA) has a positive insignificant effect (4) the influence of Debt To Asset Ratio (DAR), Current Ratio (CR) and Total Asset Turnover (TATO) simultaneously to Return On Assets ( ROA) with prob 0.00000 and F-Statistic 11.82037 have a significant positive effect (5) the effect of Return On Assets (ROA) on Stock Prices has a positive and insignificant effect.